УЛС ТӨРИЙН ОРЧИН ДАХЬ ИМИЖИЙН НӨЛӨӨЛӨЛ - С.Базарпүрэв; У.Батцэрэн (Politology, 2023)
What is the image of the politician? What is the image of the political party that image? How was it formed?, If that formed image which has been increased and decreased, or changed into disposal?, such mentioned questions are much attracted by the politicians and political scientists and other actors. Politicians and political parties attempted to seek in increasing their interactions to the public views or perception which has been formed as a positive relationship and connections with them. Consequently, there are mentioned actors such as politicians, candidates, political parties are paid strongly attention their emphasis to creating images. The personal image, personal characteristics, and factors that affects to the nominated candidate's appearance has been competed his/her political marketing code as a mirror to show up his/her whether dressing, mental thinking skills, standard of literature/speech, platforms and visional promises of the political party and party candidate, opportunities of the nominated candidates, biographies and reputation, education, business and professional skills, and demonstrate or political election. In the modern society, that political role or interactions of community organizations are increasingly expanded in the scope of impacts and its working environment. So, the understanding of the image and its role/interactions in the society are strongly admired by the politicians to focusing on this aspect.